Gender identity: challenges and limits to the inclusion policies in high school in Buenos Aires city, Argentina - Jesica Baez (Punto Género, 2017)
This article aims to explore the educational experience at High School (Public) trans youth are recognized as transvestites, transsexuals, transgender or trans masculinity or femininity in the Buenos Aires City, Argentina. For it built this empirical corpus constituted by reconstruction case of a student, a series of informal interviews students and teachers, observations of field work in High Public School of Buenos Aires between 2009 and 2012, documents, and finally a series of statistics compiled by social organizations that fight for the rights of trans characters and the results of the pilot of the First National Population Survey trans test: Transvestites, Transsexuals and Transgender INDEC - INADI (2012).